O uso do celular na escola: a implementação de um projeto de letramento nos anos finais do ensino fundamental - Juliana Machado Anastácio Souza (2015)
Faced with the imperative need to reframe pedagogical practices in teaching Portuguese language that result in the production of artificial texts - and that tends to discourage students - this paper proposes and investigates the implementation of a literacy project (Kleiman, 2002), here viewed as a set of activities which calls for reading and writing as social practices. Thus, the actions taken emerge from the real needs of students, contributing to improve themselves as protagonists of their texts Therefore, conceiving language as interactional practice, we based on studies of authors such as Bakhtin (2006), Kleiman (2010) and Tinoco (2009). The purpose of this project is directed specifically to 8th graders from a public school of Brumadinho, MG, who saw the emergence of a contentious issue around the mobile phone use in school, which led to the literacy project focused on this search. Our analysis of the project in question indicate that although this perspective presented some challenges in its implementation, such as the difficulty in overcoming barriers imposed by a school traditionalism, it is a potential way for the teaching of writing, as it mobilizes students to write, with specific purposes, covering own interests; moreover, there has been some progress in their textual capabilities. We hope to contribute to new thinking about the most effective practices for teaching writing, with support in linguistic theories, enabling renewed possibilities for pedagogical practices in teaching Portuguese.